Changes in Macular Pigment Optical Density as a New Risk Factor for Primary Open-angle Glaucoma - I. A. Loskutov; O. M. Andryukhina (Oftalʹmologiâ, 2025)
With aging, the prevalence of eye diseases such as primary open-angle glaucoma (POAG) and age-related macular degeneration (AMD) increases, making them leading causes of vision loss in older adults. Recent studies suggest that a decrease in macular pigment optical density (MPOD), composed of lutein, zeaxanthin, and meso-zeaxanthin, may be associated with an increased risk of POAG. These carotenoids play a crucial role in protecting photoreceptors from oxidative stress, regulating light filtration, and providing neuroprotection. Studies have shown that patients with POAG exhibit lower MPOD levels, which may serve as an early biomarker of glaucomatous neurodegeneration. Moreover, supplementation with macular carotenoids has been found to increase MPOD, potentially improving visual function. Additionally, B vitamins and niacin offer further protection by supporting mitochondrial health and reducing oxidative stress in retinal ganglion cells. Thus, investigating MPOD as a modifiable risk factor for POAG presents new opportunities for disease diagnosis and management. Further research is needed to determine optimal nutraceutical strategies and to evaluate the impact of MPOD on glaucoma progression.